Video Enhanced Activity Schedules: Teaching Schedule Following and Pretend Play Skills to Children with ASD - DALGIN, ÖZLEM; Ülke-Kürkçüoğlu, Burcu (Council for Exceptional Children, 2021)
The purpose of this study was to evaluate the effects of using video-enhanced activity schedules on a laptop on the acquisition, maintenance, and generalization of schedule following, and pretend play skills in children with ASD. In addition, social validity data were collected from the teachers and the mothers of the participating children. Four children with ASD, aged between 5 and 8 years, participated in this study. A multiple probe design across participants was used. The findings demonstrated that video-enhanced activity schedules on the laptop were effective in acquiring schedule following and three pretend play skills, (tea time, hairdressing, and railway train). In the study, all children maintained and generalized targeted skills across different settings and materials. The teachers and mothers of children reported positive opinions on the acceptability of the intervention and the importance of outcomes achieved. The results suggest that using video enhanced activity schedules for teaching both schedule following and pretend play skills at the same intervention sessions is an effective intervention for some children with autism. Future research implications are discussed.
Keywords: Autism Spectrum Disorders; Visual Activity Schedules; Acquisition